Analysis of organic farming practices in cocoa in India - Jaganathan, D.; Thamban, C.; Jose, C.T.; Jayasekhar, S.; Muralidharan, K.; Chandran, K. P. (Journal of Plantation Crops, 2015)
The study was conducted among 120 cocoa growers drawn randomly from one district each from Tamil Nadu, Kerala, Andhra Pradesh and Karnataka states. Profile characteristics of farmers were quantified based on socio-personal, psychological and economic variables. Majority of farmers were middle aged (64.2%), literate (96%), with less than 2 ha area under cocoa (64%) and farmers having livestock (77%). Most of the farmers had medium level of social participation, extension orientation and mass media exposure. One fifth of farmers had undergone training on organic farming, soil testing was done by nearly 31 per cent farmers and very few farmers (5%) had done organic certification. Mulching and use of green leaf manure were the main agronomic practices. Main organic inputs which were produced or prepared at the farm were, farm yard manure, crop residues, cow dung slurry, ash and vermicompost. Farm yard manure, neem cake, biofertilizers, goat manure etc. were the major inputs which were purchased from the market. Majority of cocoa growers (68.3%) had medium level of knowledge about organic farming practices. Knowledge of farmers on biocontrol agents (35%), botanical pesticides (33.3%) and biofertilizers (31.7%) was recorded. Variables like, education, social participation, extension orientation, mass media exposure and training attended were found to have positive and significant relationship with knowledge on organic farming practices. The mean yield and productivity of cocoa was found to be 1.2 kg dry beans tree-1year-1 and 608 kg dry beans ha-1 respectively. Gross income from cocoa was calculated as `170 tree-1year-1 and ` 83377 ha-1. Non-availability of labour, non-availability of quality organic inputs, difficulty in controlling pests and diseases by organic methods and lack of knowledge about organic farming practices were the major constraints.